2010
DOI: 10.1212/wnl.0b013e3181fd62d2
|View full text |Cite
|
Sign up to set email alerts
|

GFAP and S100B are biomarkers of traumatic brain injury

Abstract: This study confirms that GFAP and S100B levels in serum are adjuncts to the assessment of brain damage after TBI and may enhance prognostication when combined with clinical variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
209
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(221 citation statements)
references
References 39 publications
5
209
3
4
Order By: Relevance
“…In unfavorable compared to favorable outcome, GFAP was increased 20-fold and S100B was increased 2-fold. 20 Mean serum concentrations at hospital admission after SAH were increased (S100B threefold and GFAP twofold) compared with the upper limit of normal reference values. 21 Vos and colleagues reported that, in severe TBI patients, median serum levels of S100B, GFAP, and NSE were raised 18-fold (S100b), 5-fold (GFAP), and 2-fold (NSE), respectively, compared with normal reference values.…”
mentioning
confidence: 89%
“…In unfavorable compared to favorable outcome, GFAP was increased 20-fold and S100B was increased 2-fold. 20 Mean serum concentrations at hospital admission after SAH were increased (S100B threefold and GFAP twofold) compared with the upper limit of normal reference values. 21 Vos and colleagues reported that, in severe TBI patients, median serum levels of S100B, GFAP, and NSE were raised 18-fold (S100b), 5-fold (GFAP), and 2-fold (NSE), respectively, compared with normal reference values.…”
mentioning
confidence: 89%
“…The inflammatory protein S100 is identified as a good prognostic factor of neurological outcome after cardiac arrest and an early predictor of brain damage (11). S100 is a sensitive parameter for brain damage, and high levels of S100 in CSF and other biological fluids are associated with fatal outcome (12). Anticipating that a high vs. low S100 concentration is indicative of a more severe brain damage and injury, our results suggest that 90 s of only ventilation is too long without chest compressions to push blood out so that oxygenated blood can circulate to organs (including the brain) and peripheral tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of brain inflammation markers is somewhat limited but includes cytokines that rise within few hours after an inflammatory event (TNF-α and IL-6) (7-10); S100 (11,12), indicative of poor neurological outcome; ICAM-1 (15-17); the apoptosis pathway gene (caspase 3) (14); and MMPs (13,14), known to rise in pigs after hypoxia and reoxygenation. In group 3 (90 s), the CSF markers S100, IL-6, and TNF-α were elevated as compared with the reference group, and in the hippocampus tissue, MMP-9 and ICAM-1 genes appeared significantly differently expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100B protein in the serum of patients with traumatic brain injury (TBI) will rise rapidly within 6 hours after injury. Studies[9,10] have proved that the higher level of S100B protein in serum, the more risks the patients with TBI. It is also reported that S100B protein could predict the prognosis of patients with TBI.…”
Section: Introductionmentioning
confidence: 99%